2022
DOI: 10.1111/jan.15380
|View full text |Cite
|
Sign up to set email alerts
|

Didn't put a label on it: Examining intimate partner strangulation within a diagnostic framework

Abstract: Aims:The aim was to examine and describe women's emergency department visits and care-seeking experiences, including recognition, evaluation and communication of symptoms, injuries and health risks after non-fatal intimate partner strangulation.Design: Using a diagnostic process framework, this mixed-methods study explores concordance and discordance of interview and medical records data to highlight opportunities for clinical diagnostic improvement. Methods:In-depth, semi-structured interviews with women afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The means and methods employed were consistent with a strangulation attempt, accomplished by tugging on a cable with a knot situated on the left side of the neck. The experimental model ultimately concluded that the amount of force applied, irrespective of the victim's attempts at self-defense, exceeded 5 kg, and was enough to cause blood vessels in the neck to constrict [ 10 - 14 ]. These findings were presented in Court as scientific evidence that the manner and force of the strangulation were indeed consistent with an attempted murder [ 15 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The means and methods employed were consistent with a strangulation attempt, accomplished by tugging on a cable with a knot situated on the left side of the neck. The experimental model ultimately concluded that the amount of force applied, irrespective of the victim's attempts at self-defense, exceeded 5 kg, and was enough to cause blood vessels in the neck to constrict [ 10 - 14 ]. These findings were presented in Court as scientific evidence that the manner and force of the strangulation were indeed consistent with an attempted murder [ 15 - 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, for nurses working with perpetrators of violence, a nurse-led, 15-session videoconference-delivered cognitive behavioural group therapy is also showing promise as an intervention where participants report high levels of satisfaction and completion (Nesset et al, 2023). For women who receive care after non-fatal strangulation in an emergency department, forensic nurse examiners have a critical role in assessing symptoms and injuries, communicating diagnoses, validating patient experiences and ensuring a thorough and objective documentation of their findings (Patch et al, 2023).…”
Section: Org Aniz Ational Supp Ort For Ipv Interventi On Smentioning
confidence: 99%